Buffered Versus Non Buffered Lignocaine with Adrenaline for Pain Control in Hand Surgery: A Comparative study - Chaurasia, Lok Raj; Nakarmi, K.; Shrestha, S.; Rai, S.M. (Janaki Medical College Journal of Medical Science, 2019)
Background and Objectives: Patients with hand injuries and other conditions presenting to ER or office are usually given local anaesthesia to evaluate the case or perform a certain procedure. Lignocaine in various concentrations with or without adrenaline is used. Lignocaine with adrenaline is shown to be more acidic than plain lignocaine of similar concentration causing more pain. Sodium bicarbonate has been shown to decrease the pH of lignocaine hence decrease the pain related to injection. So this study is carried out to compare buffered (sodium bicarbonate) and plain lignocaine with adrenaline for pain control and analgesia for patients undergoing hand surgery. Material and methods: Patients in the age group of 18-60 years were divided into two groups- a control group (receiving lignocaine hydrochloride with adrenaline) and a study group (receiving carbonated lignocaine with adrenaline) and were evaluated for pain at the site of injection, onset of action of the anesthetic and its duration of analgesia and anaesthesia. Results: A total of 38 patients were included, 19 in each group. There was a significant difference in the pain score at time of injection between study group and control group (median,range: 2( 1-5) and 7(4-9) respectively ) with p<0.001. However, there was no significant difference in terms of onset of action, duration of anaesthesia and return of pain sensation. One patient developed swelling over wrist joint who received buffered solution. Conclusion: Local anesthetics used routinely in hand department should be buffered with sodium bicarbonate to reduce pain on injection of drugs in the patients.